2019
DOI: 10.1007/s10943-019-00874-y
|View full text |Cite
|
Sign up to set email alerts
|

Go in Peace: Brain Death, Reasonable Accommodation and Jewish Mourning Rituals

Abstract: Religious objections to brain death are common among Orthodox Jews. These objections often lead to conflicts between families of patients who are diagnosed with brain death, and physicians and hospitals. Israel, New York and New Jersey (among other jurisdictions) include accommodation clauses in their regulations or laws regarding the determination of death by brain-death criteria. The purpose of these clauses is to allow families an opportunity to oppose or even veto (in the case of Israel and New Jersey) det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…5,18,26,27 Failing to respect and accommodate these diverse values and beliefs can have a profound negative impact on surviving parents and family members. 6,18,25,27 Although routine integration of organ donation can conflict with religious beliefs, some commentators believe that religious beliefs should not ''be allowed to stonewall a secular approach'' to the end-of-life care of children in a multicultural society. 28 Other commentators have downplayed the conflict with religious beliefs by claiming that donating a child's organs can lessen parental bereavement symptoms.…”
Section: Cultural and Religious Challengesmentioning
confidence: 99%
“…5,18,26,27 Failing to respect and accommodate these diverse values and beliefs can have a profound negative impact on surviving parents and family members. 6,18,25,27 Although routine integration of organ donation can conflict with religious beliefs, some commentators believe that religious beliefs should not ''be allowed to stonewall a secular approach'' to the end-of-life care of children in a multicultural society. 28 Other commentators have downplayed the conflict with religious beliefs by claiming that donating a child's organs can lessen parental bereavement symptoms.…”
Section: Cultural and Religious Challengesmentioning
confidence: 99%
“…Participants were leaders of African Nova Scotian, LGBTQ2S+ (Lesbian, Gay, Bisexual, Trans, Queer, Two Spirit and others) and Faith-based (Islamic, Jewish) communities. Understanding the view of leaders from these communities is particularly important given: (1) a long and well-documented history of racial discrimination against African Nova Scotians by public institutions within the province20 21; (2) Health Canada’s decades-long and recently abandoned policy restricting sexually active men who have sex with men (MSM) from donating blood22 and (3) questions surrounding the religious permissibility of organ and tissue donation in Muslim and Jewish faiths 23 24…”
Section: Methodsmentioning
confidence: 99%
“…A survey of Jewish faith leaders found that, although 97% of rabbis know that BD and cardiopulmonary death are medically and legally equivalent, one in four believe that BD is not equivalent to death and almost one in five agrees with the continuation of life support after BD determination [ 19 ]. Opposition to BD and discontinuation of life support is particularly extended among Ultra-orthodox Jews [ 10 ]. Among Muslim faith leaders, although a majority of scholars and medical organizations accept BD as true death, the consensus is not unanimous [ 8 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., the states of New York, California, and Illinois go a step further by including accommodation clauses in their regulations or laws, the extent and duration of which are usually left to the discretion of hospitals themselves. Israel and the state of New Jersey go even further by including an option for religiously based dissent in the law, meaning that an individual who would be considered dead according to medical standards may remain legally alive if relatives veto the determination of BD on religious grounds [ 10 , 18 ]. As a matter of fact, this is a form of pluralism with regard to the legal determination of death.…”
Section: Introductionmentioning
confidence: 99%